Sustainable Management of Household Garbage- Status of Citizens behavior and participation A Case Study of Khenifra region – Morocco - Elhamdouni Driss; Arioua Abdelkrim; Aba Baaddi; Karaoui Ismail; Ait Ouhamchich Kamal; Elfiraoui Fatiazahrae (European Scientific Journal, ESJ, 2018)
Like the other Moroccan territories, Khenifra region faces many problems in household waste management, due to produced waste quantities, the insufficient infrastructure and the low level of environmental education. Khenifra region contain a diversified and fragile natural environment. In this work, we used the social approach that aims to diagnose the current state of waste management in the study area and in order to propose appropriate solutions for a successful management, as results, the existence of several deficiencies and constraints in the daily operations of collection and landfilling. Surveys and field visits have been carried out showed that the human and material resources used in the west management operation are not sufficient and not respect the environmental conditions. Facing these constraints require, an effective strategy for management of household waste in this territory has been developed to ensure a better collect and treatment. Thus, our proposed strategy cannot succeed without population involved, it requires collaboration between municipalities, delegated companies and citizens as well.